2020
DOI: 10.1002/bip.23415
|View full text |Cite
|
Sign up to set email alerts
|

FRET‐MC: A fluorescence melting competition assay for studying G4 structures in vitro

Abstract: G-quadruplexes (G4) play crucial roles in biology, analytical chemistry and nanotechnology. The stability of G4 structures is impacted by the number of G-quartets, the length and positions of loops, flanking motifs, as well as additional structural elements such as bulges, capping base pairs, or triads. Algorithms such as G4Hunter or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…In a very recent report, Luo et al also explored the competitive nature of FRET-melting and studied whether the interaction between a fluorescent G4-forming oligonucleotide and PhenDC3 is modified by a competitor sequence added in excess [ 202 ]. Sixty-five sequences with a known structure were tested to validate this FRET-melting competition (FRET-MC) assay.…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…In a very recent report, Luo et al also explored the competitive nature of FRET-melting and studied whether the interaction between a fluorescent G4-forming oligonucleotide and PhenDC3 is modified by a competitor sequence added in excess [ 202 ]. Sixty-five sequences with a known structure were tested to validate this FRET-melting competition (FRET-MC) assay.…”
Section: Methods To Characterize G4/ligand Interactionsmentioning
confidence: 99%
“…FRET melting curves ( Figure 3 ) confirmed that BPBA is able to stabilize the G4 structure formed by telomeric RNA (Δ T m = 3.4 (±0.1) °C). Moreover, to further confirm the selectivity of BPBA for G4 over the duplex, a competition FRET melting experiment was carried out in the presence of a large excess of a duplex model, i.e., a 27-mer hairpin duplex-forming DNA ( Hrp 27 ) [ 61 , 62 , 63 , 64 ]. The results of this experiment clearly showed that the stabilizing effect of BPBA on TERRA G4 was not affected by the presence of the duplex competitor ( Table 1 ), meaning that this compound preferably binds to G4s.…”
Section: Resultsmentioning
confidence: 99%
“…The oligonucleotide was dissolved in water at 1 mM, diluted at 1 μM using 5 mM potassium phosphate buffer (pH 7.0) containing 20 mM KCl, and lastly annealed by heating to 90 °C for 5 min, followed by cooling to room temperature overnight and storage at 4 °C for 24 h before data acquisition. Experiments were performed in sealed quartz cuvettes with a path length of 1 cm by using 0.2 μM of prefolded F-TERRA-T G4 target, the ligand at 2 μM, and the Hrp 27 duplex competitor at 0, 6, and 20 μM final concentrations [ 61 , 62 , 63 , 64 ]. In addition, a blank with no compound or competitor was also analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…G-quadruplexes (G4) are structures formed by guanine-rich areas and were named after the π-π interactions among the stacks, each of which contains four guanine bases. The principle of FRET has been applied to distinguishing inter-and intramolecular G4 in bulk solution since 2002 [105] and is still an efficient way to test the formation process of G4 in various conditions [106,107].…”
Section: G-quadruplex Of Telomeresmentioning
confidence: 99%